1986
DOI: 10.1093/auk/103.3.506
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Body Mass and Survival of Wintering Canvasbacks

Abstract: Mass and recapture histories of 6,000 Canvasbacks (Aythya valisineria) banded in upper Chesapeake Bay were used to test two hypotheses: (1) early-winter body mass is associated with the probability of surviving the winter, and (2) early-winter body mass is associated with annual survival probability. Data were analyzed by a binary regression method that treated mass as a continuous variable and estimated parameters to describe a general relationship between body mass and survival probability. Results for adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(56 citation statements)
references
References 19 publications
3
52
1
Order By: Relevance
“…In the case of the eider, these include (i) selecting a diet that permits a higher energy intake, (ii) minimizing the energy expended, and (iii) increasing the time spent foraging. Recent evidence supports the hypothesis that body mass (and reserves) in ducks in winter is positively correlated with the probability of survival (Haramis et al 1986;Hepp et al 1986). Eiders may in some way minimize energy expenditure to decrease the energy gain required for energy balance.…”
Section: Strategies and Conclusionsupporting
confidence: 55%
“…In the case of the eider, these include (i) selecting a diet that permits a higher energy intake, (ii) minimizing the energy expended, and (iii) increasing the time spent foraging. Recent evidence supports the hypothesis that body mass (and reserves) in ducks in winter is positively correlated with the probability of survival (Haramis et al 1986;Hepp et al 1986). Eiders may in some way minimize energy expenditure to decrease the energy gain required for energy balance.…”
Section: Strategies and Conclusionsupporting
confidence: 55%
“…A reviewer raised the question whether our results were biased because of differential migration of light birds out of the study area vs heavy birds remaining there (see also Haramis et al 1986). This notion, at first, seems difficult to resolve except that if it were true, the analysis should have reflected such a differential migration, i.e., only heavy birds would have been accessible to trapping operations and thus the z scores would have indicated that heavy birds had higher (i than lighter birds.…”
Section: Resultsmentioning
confidence: 99%
“…Weatherhead and Ankney (1984) suggested that p is different for each bird dependent on the body mass of that individual. For an in-depth description of these models and for the testing procedures used, refer to Haramis et al (1986). If this pattern were true for Black Ducks, the separation of Oi and pi would be difficult and thus, the relationship between 0i and 4D would be unclear.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if animals of a particular age at some time represent a heterogeneous mix of survival probabilities, then at some later time (age), we would expect the cohort to be composed of more individuals with higher survival probabilities (Vaupel and Yashin 1985, Johnson et al 1986, Burnham and Rexstad 1993. Of course, if the heterogeneity in survival probability is associated with an observable covariate (e.g., body size or mass; Haramis et al 1986), then separate estimation of age effects should be possible. Because the high-survival individuals would constitute increasing proportions of the surviving birds as age increased, this scenario could produce the appearance of no age-specific decline in survival probability, despite the existence of such decline within each individual.…”
Section: Discussionmentioning
confidence: 99%